The effect of several bivalent cations on the sensitivity of Rana ridibunda frog liver arginase towards proteolysis - A. S. Shamirian; R. G. Grigoryan; E. Kh. Barseghyan; M. A. Davtyan (ՀՀ ԳԱԱ հրատ.)
In the current study the products of Rana ridibunda adult frog liver arginase hydrolysis by trypsin were investigated in order to obtain information about the polypeptide chain scroll level, as well as conformation of the enzyme under consideration. Ժել -ֆիլտրացիայի եղանակով (Sephadex G-200) հետազոտվել են Rana ridibunda հասուն գորտի լյարդի տրիպսինով հիդրոլիզի արգասիքները, նպատակ ունենալով ստանալ տվյալներ պոլիպեպտիդային շղթայի պարուրման աստիճանի և հետազոտվող ֆերմենտի կոնֆորմացիայի մասին: С целью получения информации о степени свернутости полипептидной цепи и о конформации макромолекулы аргиназы печени взрослых лягушек Rana ridibunda методом гель фильтрации на колонках с сефадексом G-200 исследовали продукты триптического гидролиза изучаемого фермента.
Keywords: Biology; Biochemistry; Physiology